Pengaruh Suplementasi Vitamin C dan Jarak Transportasi Terhadap Penyusutan Bobot Badan Broiler - Nur Kholis; Ujang Suryadi; Faturrahman Roni (Politeknik Negeri Jember, 2018)
The purpose of this study was to know the effect of vitamin C supplementation and distance transportation on broiler weight loss. The method used in this study using 128 days of unisexing broiler. The experimental design used a Factorial Completely Randomized Design. The experimental factor consisted of 2 factors, such as the distance factor with 2 levels, 24 km (a1) and 48 km (a2), and the sumplemetation factor of vitamin C with 4 levels such as 0 mg/L (b1), 250 mg/L (b2), 500 mg/L (b3), and 750 mg/L (b4). The experiment was 4 times replication. If obtained significantly result, continued by Least Significant Difference test (LSD). Vitamin C supplementation was significant to weight loss, heart rate, glucose, and mortality in broilers during transportation. The transportation mileage was significant to weight loss and heart rate in broilers. Supplementation of vitamin C and transportation mileage provided a significant interaction weight loss, heart rate, glucose, and mortality in broilers.